The Effect of Using Brainly Media on Argumentative Text Writing Skills in Class XI of SMA Negeri 1 Mardingding - Chornelyus Dehouq Simorangkir; Harlen Simanjuntak; Elza Leyli Lisnora Saragih (Raja Zulkarnain Education Foundation, 2026)
Brainly is a peer-to-peer (between students) based social learning platform and educational application that allows users to ask and answer questions about homework or school materials. As a learning medium, Brainly becomes a means of collaboration where students help each other understand the material, exchange information, and solve academic problems. This study aims to describe: 1) the results of the pre-test of the ability to write argumentative texts; 2) the results of the post-test of the ability to write argumentative texts in learning using the Brainly application media. This study uses a quantitative method through a quasi-experiment using One Group Pretest-Posttest Design in the 2025/2026 academic year at SMA Negeri 1 Mardingding. The population of this study was all students of class XI.A SMA Negeri 1 Mardingding who took the pre-test, learning the ability to write argumentative texts using the Brainly application media, and took the post-test of the ability to write argumentative texts, totaling 34 students. The sample was determined at 32 students based on a statistical formula. The research instruments were news text writing tests and lesson plans as well as the Brainly application media. The research data were analyzed using parametric inferential statistics, namely one-sample t-test for the first and second objectives and paired sample t-test for the third objective. All test requirements, namely normality and homogeneity, were met. The results of the study showed: 1) the mean pre-test of the ability to write news texts of class XI.A students of SMA Negeri 1 Mardingding was 16.84 or 52.63 percent (categorized as low); 2) the mean post-test of the ability to write news texts of class XI.A students of SMA Negeri 1 Mardingding was 26.00 or 81.25 (categorized as high); 3) the brainly application media was proven to be effective in learning the ability to write argumentative texts. The t-value of the paired sample test was -19.363 with a sig. 0.00 <0.05 so that Ho was rejected.